Effect Of Consumption Of Commercially Packed Cow′s Milk On Thyroid Hormone Homeostasis - Chudhuri R N; Bhattacharyya Piyali (Wolters Kluwer Medknow Publications, 1999)
Research question: Whether consumption of commercially packed cowâ€s milk containing thiocyanate as a preservative, has any effect on thyroid function? Objective: To assess the effect of ingestion of thiocyanate through commercially packed cowâ€s milk on thyroid hormone homeostasis. Study Design: Cross sectional. Setting: Urban slum community of Calcutta. Participants: Randomly selected 30 teenage girls consuming commercially packed cowâ€s milk since childhood and ideally matched 30 control subjects consuming non-pack cowâ€s milk since childhood from an urban slum community of Calcutta. Results: Consumption of commercially packed cowâ€s milk was found to inhibit thyroxin synthesis.